The Stochastic Decomposition Results of Markovianbatch Arrival Queueing System with a Grand Vacation Process and State Dependent Arrival Rate - Dr. Raj Kamal Gupta (International Journal of Advanced Science and Technology, 2020)
In this investigation, we analyze the batch arrival poisson Queneing system with a grand vacation process and state dependent arrival rate. We establish some stochastic decomposition result for a class of batch arrival quequing system with a grand vacation process. These results are derived at various points of time, for example random point of time, departure point of time, stationary point of time etc. Some special cases are also provided which match with earlier existing results.